1993
DOI: 10.1007/bf03160027
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic study on dopamine uptake sites and their correlation with dopamine levels and their striata from patients with Parkinson disease, Alzheimer disease, and neurologically normal controls

Abstract: An autoradiographic study of labeled mazindol binding to presumed dopamine (DA) uptake sites in the striatum was done in 7 Parkinson (PD), 6 Alzheimer (AD), 1 Huntington disease (HD), and 4 neurologically normal cases. Large and significant decreases of specific binding were found in PD in both caudate (to 32% of control) and putamen (to 16%), with no significant effect in AD or HD. Nonspecific binding was a large proportion of total binding in all cases. In the 12 cases where both binding data and DA levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…The morphologically-demonstrated loss of neurons in the pars compacta of the SN correlates significantly with the reduction of dopamine in the Mizukawa et al (1993) DOPA 3,4-dihydroxyphenylalanine, DOPAC 3,4-dihydroxyphenylacetic acid, HVA homovanillic acid. *For further reading and original data see references indicated in Table 1 striatum, and the extent of the dopamine deficit correlates with the degree of akinesia (Bernheimer et al, 1973).…”
Section: Changes In Dopaminergic Systemsmentioning
confidence: 98%
“…The morphologically-demonstrated loss of neurons in the pars compacta of the SN correlates significantly with the reduction of dopamine in the Mizukawa et al (1993) DOPA 3,4-dihydroxyphenylalanine, DOPAC 3,4-dihydroxyphenylacetic acid, HVA homovanillic acid. *For further reading and original data see references indicated in Table 1 striatum, and the extent of the dopamine deficit correlates with the degree of akinesia (Bernheimer et al, 1973).…”
Section: Changes In Dopaminergic Systemsmentioning
confidence: 98%
“…In the hypothalamus, the D2 receptor binding potentials were also significantly reduced without a correlation with age and levodopa equivalent dose (Politis et al, 2008). Mizukawa et al reported a significant reduction in the density of dopamine receptors in both the caudate and putamen of advanced PD patients (Mizukawa et al, 1993); while Boileau et al found decreased dopamine D3 receptor binding in the ventral striatum and globus pallidus in drug-naive PD patients (Boileau et al, 2009). …”
Section: Alterations In Neurotransmitter Receptors In Parkinson’s mentioning
confidence: 99%
“…[2][3][4] In addition, a reduction of striatal dopamine reuptake sites has been found in postmortem studies using various ligands in AD patients 5 and in patients with AD and parkinsonism, 6 but no significant decrease in the striatal dopamine uptake sites in AD was found in another study. 7 Molecular techniques have revealed the existence of at least five different dopamine receptor subtypes. These receptors are named D1-D5 receptors and are divided in broad terms into "D1-like" (D1 and D5) and "D2-like" (D2, D3, D4) receptors.…”
mentioning
confidence: 99%